The Assembly of C60 in Semicrystalline PLLA Matrix - Chen, Li; Pang, Xiujiang (Nano-Micro Letters, 2012)
It has increasingly become a research focus to build higher structure composed of C60. However, there has been very few reports on the influence of polymer addition on the self-assembling behavior of fullerene in organic solvents. In this research, big needle-like C60 assemblings have been obtained in the form of PLLA/C60 composites. The largest C60 needles can be observed by naked eyes. The amount of C60 in the composite influences the length of C60 needles to some extent. DSC results indicate C60 accelerates the crystallization and lift the relative crystallinity of PLLA matrix. the results also imply the addition of semicrystalline PLLA influence the assembling behavior of C60. i.e., the crystallization of PLLA accelerated by C60 also act a driving force for the enriching and the linear assembling of C60 in PLLA matrix via Van der Waals force.